2001
DOI: 10.1139/bcb-79-6-709
|View full text |Cite
|
Sign up to set email alerts
|

Cell death and survival alterations in Malpighian tubules of <i>Triatoma infestans</i> following heat shock

Abstract: In this study, we examined cell survival and cell death in response to heat shock in an insect organ composed of highly polyploid cells no longer capable of cell division. For this, the frequency of nuclear phenotypes in Feulgen-stained Malpighian tubules of the blood-sucking insect, Triatoma infestans, was analyzed at various times after a short heat shock with or without subsequent moderate fasting. Cell death DNA fragmentation was studied immunocytochemically. Normal phenotypes and phenotypes indicative of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The unpackaging of heterochromatin, a phenomenon that was previously reported as a cellular survival response to stress factors in the Malpighian tubules of Triatomini (Mello et al, 1995(Mello et al, , 2001, was observed under all tested conditions. However, the frequency of nuclei with heterochromatin unpackaging one and 48 h following the 5-AZA treatment exceeded the frequency observed in the untreated controls or in DMSO-treated nymphs.…”
Section: Cytidine Demethylation Assaysupporting
confidence: 65%
See 4 more Smart Citations
“…The unpackaging of heterochromatin, a phenomenon that was previously reported as a cellular survival response to stress factors in the Malpighian tubules of Triatomini (Mello et al, 1995(Mello et al, , 2001, was observed under all tested conditions. However, the frequency of nuclei with heterochromatin unpackaging one and 48 h following the 5-AZA treatment exceeded the frequency observed in the untreated controls or in DMSO-treated nymphs.…”
Section: Cytidine Demethylation Assaysupporting
confidence: 65%
“…The acid hydrolysis time used allowed for the maximal DNA depurination for this material as reported previously (Mello et al, 2001). The Feulgen-stained material was rinsed in three baths (5 min each) of sulfurous water and one bath of distilled water, air dried, cleared in xylene, and mounted in natural Canada balsam (n D = 1.54).…”
Section: Feulgen Reactionmentioning
confidence: 99%
See 3 more Smart Citations